2004 and 2008 general elections in Malaysia: towards a multicultural, bi-party political system? - Moten, Abdul Rashid (2009)
The Barisan Nasional (BN), which won a landslide victory in 2004, was returned to power in the 2008 elections with reduced majority and the loss of five state assemblies. Dissatisfied with unfulfilled promises, the electorate protested by voting for a strong opposition. BN was additionally characterized by factionalism. Three major opposition parties joined hands on a platform of multiculturalism and, using alternative media, unexpectedly, won 82 seats in the parliament. A strong responsible opposition bodes well for multiculturalism and Malaysian democracy